A Supervisor-Targeted Implementation Approach to Promote System Change: The R(3) Model - Saldana, Lisa (Adm Policy Ment Health, 2016)
Opportunities to evaluate strategies to create system-wide change in the child welfare system (CWS) and the resulting public health impact are rare. Leveraging a real-world, system-initiated effort to infuse the use of evidence-based principles throughout a CWS workforce, a pilot of the R(3) model and supervisor-targeted implementation approach is described. The development of R(3) and its associated fidelity monitoring was a collaboration between the CWS and model developers. Outcomes demonstrate implementation feasibility, strong fidelity scale measurement properties, improved supervisor fidelity over time, and the acceptability and perception of positive change by agency leadership. The value of system-initiated collaborations is discussed.